Learning leadership the five fundamentals of becoming an exemplary leader - James M. Kouzes, Barry Z. Posner (Hoboken, NJ Wiley, 2016)
The book offers a concrete framework to help individuals of all levels, functions, and backgrounds take charge of their own leadership development and become the best leaders they can be. Arguing that all individuals are born with the capacity to lead, Kouzes and Posner provide readers with a practical series of actions and specific coaching tips for harnessing that capacity and creating a context in which they can excel., Supported by over 30 years of research, from over seventy countries, and with examples from real-world leaders, Learning Leadership is a clarion call to unleash the leadership potential that is already present in today s society. According to Kouzes and Posner, Leadership makes a significant difference in levels of engagement and commitment and is perhaps the most important asset in every organization, yet recent research points to a shortage of leaders. It is a serious global concern. The world needs more exemplary leaders in order to promote high-performing workplaces and inspire feelings of greater self-worth and meaningfulness. The shortage, however, is not because of the lack of potential talent. The people are out there, the eagerness is out there, and the capability is out there. The shortage results from prevailing myths myths about talent, strengths, position, self-reliance, and effort that inhibit the vast majority of leaders from shining and organizations from realizing the full benefits of the talent they already have. Learning Leadership provides readers with evidence-based strategies to ignite the habit of continuous improvement and the mindset of becoming the best leaders they can be. Emerging leaders, as well as leadership developers, internal and external coaches and trainers, and other human resource professionals will learn from first-hand stories and practical examples so that they can deeply understand and apply the fundamental for becoming the best leaders they can be. Learning Leadership: The Five Fundamentals of Becoming an Exemplary Leader is divided into digestible bite-sized chapters that encourage daily actions to becoming a better leader.
Includes bibliographical references and index.
Keywords: Leadership